The Association between LRRK2 G2385R and Phenotype of Parkinson’s Disease in Asian Population: A Meta-Analysis of Comparative Studies - Wei Di; Zhiyong Zeng; Jingyan Li; Xiaoling Liu; Minzhi Bo; Hua Lv (Parkinson's Disease)
Numerous studies have investigated the relationship between the LRRK2 G2385R variant and clinical characteristics in Parkinson’s disease (PD), but the results have been inconsistent. This study investigated whether the LRRK2 G2385R variant was associated with a unique clinical phenotype of PD in the Asian population, using a meta-analysis. The PubMed, Web of Science, EMBASE, CNKI, and WANFANG databases were searched until September 2017. The strict selection criteria and exclusion criteria were determined, and mean differences (MD) or odds ratios (OR) with 95% confidence intervals (CI) were used to assess the strength of associations. Statistical analyses and graphics were performed using Review Manager 5.3. Sixteen related case-control studies were included in the meta-analysis. The LRRK2 G2385R carriers significantly more often presented a family history (OR: 1.98; 95% CI: 1.16−3.39; P=0.01) and had a longer disease duration (MD = 0.47, 95% CI: 0.01−0.93, P=0.04) and a higher MMSE score (MD = 1.02, 95% CI: 0.43–1.62 P=0.0007) than LRRK2 G2385R noncarriers. There were no significant differences in sex distribution, age at onset, initial symptoms, motor symptoms, depression, levodopa-equivalent dose, and related complications between LRRK2 G2385R-carrier and LRRK2 G2385R-noncarrier PD patients. Our results suggested that most of the clinical characteristics of PD patients with LRRK2 G2385R mutations are similar to those of LRRK2 G2385R noncarriers among Asian PD patients, except for the more common family history, relatively longer disease duration, and higher MMSE scores in the former group.